2018
DOI: 10.1002/gcc.22682
|View full text |Cite
|
Sign up to set email alerts
|

Next generation sequencing of the cellular and liquid fraction of pancreatic cyst fluid supports discrimination of IPMN from pseudocysts and reveals cases with multiple mutated driver clones: First findings from the prospective ZYSTEUS biomarker study

Abstract: Approximately half of all pancreatic cysts are neoplastic, mainly comprising intraductal papillary mucinous neoplasms (IPMN), which can progress to invasive carcinoma. Current Fukuoka guidelines have limited sensitivity and specificity in predicting progression of asymptomatic pancreatic cysts. We present first results of the prospective ZYSTEUS biomarker study investigating (i) whether detection of driver mutations in IPMN by liquid biopsy is technically feasible, (ii) which compartment of IPMN is most suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Past studies [36][37][38][39] and data from our retrospective and prospective cohorts show that NGS analyses can be performed successfully on cytology smears or even cell-free cyst fluid. When comparing cfDNA samples with DNA extracted from smear samples, we found higher mean allelic frequencies of gene variants in the smear samples, probably due to higher cellularity.…”
Section: Discussionmentioning
confidence: 84%
“…Past studies [36][37][38][39] and data from our retrospective and prospective cohorts show that NGS analyses can be performed successfully on cytology smears or even cell-free cyst fluid. When comparing cfDNA samples with DNA extracted from smear samples, we found higher mean allelic frequencies of gene variants in the smear samples, probably due to higher cellularity.…”
Section: Discussionmentioning
confidence: 84%
“…The high sensitivity and specificity of the KRAS/GNAS ‐testing by dtNGS, in which all DNA‐molecules are labeled with individual barcodes before amplification, 23 is probably due to the very low limit of detection down to 0.01% VAF. Therefore, it might be more sensitive than previously used NGS approaches with a limit of detection of 3% to 5% or Sanger sequencing with a limit of detection of 10% to 20% VAF 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The wall of the PCL/MPD was only passed once for needle access to minimize PCL/MPD injury and to reduce potential access tract cell seeding (Figure 1). As we have discussed in our feasibility study, 23 a minimum cyst size of 10 to 15 mm was necessary to obtain an aspirated volume of at least 1000 μL for analysis of both CEA (≥500 μL) and cfDNA (≥500 μL). The remaining content of the hollow needle was used for cytological smear preparation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, other biomarkers sampled from cyst fluid or other sources are emerging and of interest. Particular interest is expressed in next generation sequencing of pancreatic cystic fluid[38-41]. Investigators have reported KRAS / GNAS mutations to be present in 100% of IPMNs[39] and to be highly sensitive and specific (89% and 100%, respectively) for IPMNs and mucinous cystic lesions[39].…”
Section: Informed Decision-making: a Stepwise Approachmentioning
confidence: 99%